2010
DOI: 10.1016/j.bbrc.2010.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the core single-stranded DNA-binding domain of purine-rich element binding protein B (Purβ)

Abstract: Purβ is a single-stranded nucleic acid-binding protein implicated in the injury-induced repression of genes encoding certain muscle-restricted isoforms of actin and myosin expressed in the heart, skeletal muscle, and vasculature. To better understand how the modular arrangement of the primary sequence of Purβ affects the higher order structure and function of the protein, purified recombinant Purβ was subjected to partial proteolysis in an attempt to identify a well-folded truncation protein that retained puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Despite this technical limitation, the Purβ I-II-III core construct did appear to bind PE32-F with comparable affinity and specificity to full-length Purβ under the assay conditions employed (Figure 7). Moreover, the biochemical properties of Purβ I-II-III (residues 41-303) defined in this study are analogous to those of a His tag-free core tryptic fragment of Purβ (residues 29-305) described in an earlier report (40). Interestingly, while the Purβ I-II and Purβ III subdomains each displayed a lower apparent affinity for PE32-F than Purβ I-II-III, the intermolecular subdomain bound more tightly to ssDNA than the intramolecular subdomain.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Despite this technical limitation, the Purβ I-II-III core construct did appear to bind PE32-F with comparable affinity and specificity to full-length Purβ under the assay conditions employed (Figure 7). Moreover, the biochemical properties of Purβ I-II-III (residues 41-303) defined in this study are analogous to those of a His tag-free core tryptic fragment of Purβ (residues 29-305) described in an earlier report (40). Interestingly, while the Purβ I-II and Purβ III subdomains each displayed a lower apparent affinity for PE32-F than Purβ I-II-III, the intermolecular subdomain bound more tightly to ssDNA than the intramolecular subdomain.…”
Section: Discussionsupporting
confidence: 81%
“…Multiple wavelength scans were recorded at 1 nm intervals from 195 to 280 nm on 5.0 μM protein solutions in a 1 mm cuvette at 25°C. Raw CD data were analyzed as previously described (40). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by our structural modeling, EGFR-RAD51 fusion proteins could be activated by virtue of RAD51 oligomerization. Similarly, structural modeling has shown that PURB proteins can self-associate in the absence of nucleic acids (28). Additional experimental work will be required to determine whether activation of EGFR fusion proteins is driven by asymmetric dimerization of the EGFR tyrosine kinase domain, dimerization through the known partner oligomerization interface, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated components of inflammatory response pathways, but have been met with limited success. 43 This core region of Purβ contains sequence elements termed Pur repeats I, II, and III that are highly conserved in Purα. 14,15 The transcriptional repressor protein, Purβ, is of special interest because of its unique ability to interact with specific ssDNA sequences in the Acta2 promoter and with other transcription factors that dictate Acta2 gene expression in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%